Analysis The Physical Condition of West Kalimantan Prapon Futsal Athletes - Rahmat Putra Perdana; Rubiyatno Rubiyatno; Edi Purnomo; Aris Tri Wibowo (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
The purpose of this research is this study aims to find out the extent of the physical condition of the preparation of West Kalimantan Prapon futsal athletes in making pre-PON selection so that they can pass the PON event. The sample in this study was athletes Pra PON West Kalimantan consisting of 35 people consisting of 13 men and 22 women. The research method makes the research design using the "One Shot Method" approach, which uses one-time data collection. Data collection techniques use test techniques. The data analysis techniques used in this study used quantitative descriptive statistics by percentage. The results of the data analysis can be concluded: (1) the physical condition factor of abdominal muscle strength and flexibility alone that has excellent average ability. (2). Pushing and pulling power, hand strength, limb strength, togok strength, agility have considerable average ability.  (3)  The physical components of the explosive power of the limb muscles have less average ability, (4) the physical condition factor of endurance and reaction time has  very  less ability